THE EFFECT OF TV ON CHILDREN - Khaleel, Mousa (International Journal of Psychosocial Rehabilitation, 2020)
This research paper investigates how television is associated with the behavior and development of children of age group of 5 to 15. This paper examines whether behavior, academic performance, attitude and life style of children is influenced by watching television negatively or positively. This research explores this subject through quantitative approach, data was collected with the convenience sampling from 100 of respondents by using questionnaire. Different graphs and tables indicates opinions of respondents. The results indicate that television is not solely influencing children, parents must consider moderate use of television that can be helpful for the development of their children.